2001
DOI: 10.1038/sj.bjp.0704309
|View full text |Cite
|
Sign up to set email alerts
|

α2‐adrenoceptor antagonist properties of OPC‐28326, a novel selective peripheral vasodilator

Abstract: 1 Antagonistic properties of OPC-28326 ([4-(N-methyl-2-phenylethylamino)-1-(3,5-dimethyl-4-propionyl-aminobenzoyl)] piperidine hydrochloride monohydrate), a selective peripheral vasodilator, were investigated by analysing the data from functional studies in various tissues from the rat and binding studies of the drug to a 2 -adrenoceptor subtypes. 2 Using a human recombinant receptor and rat kidney cortex, we found that OPC-28326 displays a nities to a 2A -, a 2B -and a 2C -adrenoceptors with K i values of 204… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…OPC‐28326 (4‐[N‐methyl‐2‐phenylethyl‐amino]‐1‐[3,5‐dimethyl‐4‐propionyl‐aminobenzoyl] piperidine hydrochloride monohydrate), a piperidine derivative, is a selective α‐adrenergic antagonist with preferential binding to the α 2C ‐AR subtype (α 2C is several‐fold stronger than α 2B , followed in decreasing strength by α 2A and α 1 ) (4–6). Animal studies involving OPC‐28326 have demonstrated improved hind‐limb blood flow during cold exposure and normalized skin temperature under anesthesia with this drug (6, 7).…”
mentioning
confidence: 99%
“…OPC‐28326 (4‐[N‐methyl‐2‐phenylethyl‐amino]‐1‐[3,5‐dimethyl‐4‐propionyl‐aminobenzoyl] piperidine hydrochloride monohydrate), a piperidine derivative, is a selective α‐adrenergic antagonist with preferential binding to the α 2C ‐AR subtype (α 2C is several‐fold stronger than α 2B , followed in decreasing strength by α 2A and α 1 ) (4–6). Animal studies involving OPC‐28326 have demonstrated improved hind‐limb blood flow during cold exposure and normalized skin temperature under anesthesia with this drug (6, 7).…”
mentioning
confidence: 99%
“…Our present findings indicated the possibility that prejunctional a1-adrenoceptors modulated the release of norepinephrine from sympathetic nerve terminals in rat urethra. It is accepted that prejunctional a 2 -adrenoceptors modulate the release of norepinephrine from sympathetic nerve terminals, and clonidine has been used to study this effect (18). To investigate the presence of prejunctional a 2-adrenoceptors, we also examined the effect of clonidine on the urethral pressure response to ES of the HGNs.…”
Section: Discussionmentioning
confidence: 99%
“…We also suggested that properties of the a2-adrenoceptor antagonistic action of OPC-28326 showed high selectivity for postsynapses compared to yohimbine, and OPC-28326 did not affect the central nervous action induced by an a2-adrenoceptor agonist (2). OPC-28326 showed affinities for a2A-, a2B-and a2C-adrenoceptors with Ki values of 2040, 285 and 55 nM, respectively, in receptor binding studies (2). It was reported that cooling augmented vasoconstriction induced by a2-adrenoceoptor activation and that postjunctional a2-adrenoceptors are important for thermoregulation in this vascular bed (8,9).…”
mentioning
confidence: 99%
“…This drug has little effect on other cardiovascular parameters, such as blood pressure, heart rate, contractile force of myocardium, and blood flow in other areas, such as the carotid, vertebral, coronary, renal and mesentery arteries (1). a 2 -Adrenoceptor blocking action of OPC-28326 may be involved its selective vasodilator action on the femoral artery (2). To evaluate the effects of oral administration of OPC-28326, we measured subcutaneous temperature using a wire-type thermometer in conscious dogs sedated with buprenorphine.…”
mentioning
confidence: 99%